2012
DOI: 10.1038/cmi.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

CD28 ligation increases macrophage suppression of T-cell proliferation

Abstract: When compared to spleen or lymph node cells, resident peritoneal cavity cells respond poorly to T cell activation in vitro. The greater proportional representation of macrophages in this cell source has been shown to actively suppress the T cell response. Peritoneal macrophages exhibit an immature phenotype (MHC Class IIlo, B7lo) that reduces their efficacy as antigen presenting cells. Furthermore, these cells readily express inducible nitric oxide synthase (iNOS), an enzyme that promotes T cell tolerance by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…1B). These results demonstrate the utility of this culture model for studying macrophage suppression of T cell activation [4144]. …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…1B). These results demonstrate the utility of this culture model for studying macrophage suppression of T cell activation [4144]. …”
Section: Resultsmentioning
confidence: 73%
“…For each experiment 3–5 wells were established for each test group. As noted in our prior studies [42,44], media only controls routinely had < 1000 CPM and were excluded from figures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6J PerC Mϕs temper TCR-triggered activation by inducing IFNγ-driven iNOS expression, which promotes proliferative arrest via arginine catabolism [11,12,14]. Inhibition of iNOS with 1-MA or neutralization of IFNγ abrogated PerC T cell suppression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that peritoneal cavity (PerC) T cell proliferation is suppressed by the increased representation of macrophages present in this cell source [11]. T cell proliferation is regulated via catabolism of limiting amino acids, production of anti-inflammatory cytokines, and prostaglandin production [1114]. PerC cell preparations include a significant fraction of B cells, notably the B1 subset distinctive for antibody responses to commensal microflora [15].…”
Section: Introductionmentioning
confidence: 99%